Violencia escolar entre alumnas de primero de secundaria de una institución educativa del Callao - Aranda Ponte, Esther Maritza (2010)
Violence against female students of first grade High School was investigated in an educational institution from Callao by using a descriptive research. The sample was taken from 147 female students. The variety school violence was evaluated with the hounding and school violence test of Oñate and Piñuel, whose validity was tested through the expert judgment with a confident level of 0.93. The results were analized with the statics SPS getting a 40% of students that consider that there is a high level of school violence and another 40% that there is a low level . Analyzing the four dimentions of the variety by hostility, intimidation, social exclusion and agressions. It was observed that the highest score was for intimidation.Conclusion there is school violence in a significant level. Such results suggest us that school can reduce those types of violence with an efficient control.